Homogenization of a Singularly Perturbed Parabolic Problem in a Thick Periodic Junction of the Type 3:2:1 - Mel'nik, T. A. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We prove a convergence theorem and obtain asymptotic (as ε → 0) estimates for a solution of a parabolic initial boundary-value problem in a junction Ωε that consists of a domain Ω0 and a large number N 2 of ε-periodically located thin cylinders whose thickness is of order ε = O(N −1).